Effect of Cyclic Stress Level and Overconsolidation Ratio on Permanent Deformation Behaviour of Clayey Subsoil - Lei Sun (Civil Engineering Journal, 2018)
This paper presents the results of a series of one-way cyclic triaxial tests carried out to investigate the role of cyclic stress level and overconsolidation ratio (OCR) on the permanent deformation behaviour of saturated clayey subsoil during long-term cyclic loading. Based on the test results and shakedown concept, two cyclic threshold deviator stress ratios can be defined: the plastic shakedown limit cyclic deviator stress ratio CSRpt (0.46) and the plastic creep shakedown limit cyclic deviator stress ratio CSRpc (0.75). It was found that, below CSRpt, the soil experiences slight deformation and gradually achieves a long-term steady state response. Within the range of CSRpt<CSR<CSRpc, the plastic strain will accumulates substantially and becomes unstable. Once the CSRpc is exceeded significant deformation and failure may occur. In the practical engineering, CSRpt can be used for preliminary design of pavement foundation. In addition, based on the test results, a simplified permanent axial strain model that explicitly considers the effects of CSR and OCR is developed.